RANCANGAN APLIKASI SISTEM MONITORING PELANGGARAN DAN PRESTASI SISWA SMPN 8 KOLAKA UTARA BERBASIS WEB - Titin Wahyuni; Fahmi Ramadhan S; Lukman Anas (Ainet : Jurnal Informatika, 2023)
Abstract       Technology is the result of the development of science, which occurs in the world of education. Therefore, it is appropriate that education itself also utilizes technology to assist the implementation of learning. With the development of this technology, it is easier for students, teaching staff and even parents to understand information about education, both formal and non-formal. Through this internet development, education in remote areas is able to obtain accurate information and is able to compete with the world of education, so that it can produce intelligent, responsible and disciplined students. The purpose of this research is to design a web-based violation and student achievement system application to assist the school in monitoring students and improving student discipline in complying with school rules and regulations and motivating students to excel. The Waterfall method is a classic model that is systematic, the waterfall method is serial in nature which starts from the process of planning, analysis, design and implementation of the system. This method is carried out starting from the system requirements stage and then moving on to the analysis, design, coding, testing/verification and maintenance stages. Based on the test results obtained, the design of the violation application system and student achievement was as expected. Keyword: Monitoring; Violation; Achievement; waterfalls; Website Application Abstrak       Teknologi merupakan hasil dari perkembangan ilmu pengetahuan, yang terjadi di dunia pendidikan. Oleh karena itu, sudah selayaknya pendidikan sendiri juga memanfaatkan teknologi untuk membantu pelaksanaan pembelajaran. Dengan adanya perkembangan teknologi ini membuat peserta didik, staf pengajar bahkan orang tua lebih mudah memahami informasi seputar Pendidikan baik bersifat formal maupun non formal. Melalui perkembangan internet ini, Pendidikan di daerah terpencil mampu mendapatkan informasi yang akurat serta mampu bersaing dengan dunia Pendidikan, sehingga bisa melahirkan peserta-peserta didik yang cerdas, bertanggung jawab serta disiplin. Tujuan dari penelitian ini adalah merancang aplikasi aplikasi sistem pelanggaran dan prestasi siswa berbasis web guna untuk membantu pihak sekolah dalam memonitoring siswa dan memperbaiki kedisiplinan siswa dalam mematuhi peraturan tata tertib sekolah dan memberikan motivasi siswa dalam berprestasi. Metode Waterfall adalah model klasik yang bersifat sistematis, metode waterfall bersifat serial yang dimulai dari proses perencanaan, Analisa, desain dan implementasi pada sistem. Metode ini dilakukan mulai dari tahap kebutuhan sistem lalu menuju ke tahap analisis, desain, coding, testing/verification dan maintenance. Berdasarkan hasil pengujian yang diperoleh, menghasilkan rancangan sistem aplikasi pelanggaran dan dan prestasi siswa ini sudah sesuai yang diharapkan. Kata kunci: Monitoring; Pelanggaran; Prestasi; Waterfall; Aplikasi Website